РАЗВИТИЕ ТРАНСПОРТНОЙ ИНФРАСТРУКТУРЫ В УЗБЕКИСТАНЕ КАК ФАКТОР ПОВЫШЕНИЯ КОНКУРЕНТОСПОСОБНОСТИ ЭКОНОМИКИ СТРАНЫ (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
this article reveals the factors of increasing the competitiveness of the country. In particular, the development of transport infrastructure contributes to the development of tourism, provides safe and fast transportation of passengers and cargo and thereby contributes to social development.